2015
DOI: 10.1177/1352458515586086
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multiple sclerosis exhibits decreasing glutamate and glutamine over two years

Abstract: The high rates of change of both glutamate and glutamine over two years suggest they are promising new biomarkers of MS disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 14 publications
(26 reference statements)
5
40
1
1
Order By: Relevance
“…Several MRI techniques may provide improved pathologic specificity and, thus, better correlation with clinical disability: diffusion tensor imaging (DTI, which quantifies the threedimensional diffusion of water), 34 magnetization transfer imaging (MTI, which quantifies tissue integrity through the interaction of protons bound to molecular structures and free water), 35 magnetic resonance spectroscopy (which quantifies tissue metabolites), 36 and techniques such as magnetic resonance fingerprinting. 37 These techniques can be applied to the whole brain, or selectively to gray or white matter lesions, or regions that appear normal on standard MRI.…”
Section: "Advanced" Mri Techniquesmentioning
confidence: 99%
“…Several MRI techniques may provide improved pathologic specificity and, thus, better correlation with clinical disability: diffusion tensor imaging (DTI, which quantifies the threedimensional diffusion of water), 34 magnetization transfer imaging (MTI, which quantifies tissue integrity through the interaction of protons bound to molecular structures and free water), 35 magnetic resonance spectroscopy (which quantifies tissue metabolites), 36 and techniques such as magnetic resonance fingerprinting. 37 These techniques can be applied to the whole brain, or selectively to gray or white matter lesions, or regions that appear normal on standard MRI.…”
Section: "Advanced" Mri Techniquesmentioning
confidence: 99%
“…MacMillan et al found early and consistent alterations in the Glu and glutamine levels in CNS over two years in SPMS patients with MR spectroscopy. This method might be competent to measure disease progression over years, using the appropriate imaging techniques suggested by the authors [160]. …”
Section: Biomarkers In Tissue Damage Of Msmentioning
confidence: 99%
“…More recently, however, research has begun to indicate that changes in glutamate levels and glutamate receptor expression may be significant earlier in the disease process than originally thought [10]. In one two-year study [11], the levels of both glutamate and glutamine were shown to change markedly over time in the white matter of MS patients with large decreases seen over the course of the study. Overall, the expression of those enzymes responsible for the production and degradation of glutamate is imbalanced in MS [12], potentially causing a type of positive-feedback loop in which glutamate excitotoxicity induces axonal apoptosis, releasing more glutamate [13].…”
Section: Introductionmentioning
confidence: 99%